Short-term effects of an active prosthetic solution on functional ability, level of activity and participation of children with unilateral transtibial amputations - Haywood, Gemma Jean (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.